THE INFLUENCE OF WORK ENVIRONMENT, WORK MOTIVATION, AND COMPENSATION ON JOB SATISFACTION OF GENERATION Z IN JABODETABEK - Jonathan J. Susilo; Joyce A. Turangan (Graduate Program of Universitas Tarumanagara, 2024)
Currently the world of work is seeing a major transformation with the entry of Generation Z workers who have begun to enter the world of work. Generation Z itself has unique characteristics and is different from previous generations. Job satisfaction is of course one of the things that is very important for workers because job satisfaction will affect the performance of the worker. The purpose of this research is to determine the influence of the work environment, work motivation, and compensation on Generation Z job satisfaction in Jabodetabek. The total samples obtained were 251 samples obtained using the non-probability sampling method, namely purposive sampling. The data that has been obtained is then processed using structural equation modelling (SEM) analysis which will be processed using SmartPLS software. The results of this study shows that work environment, work motivation, and compensation have a positive and significant effects on job satisfaction of Generation Z. The conclusion is that work environment, work motivation, and compensation all have an effect on Generation Z job satisfaction in Jabodetabek.